Ответы и объяснения

Лучший Ответ!
  • AlbuRin
  • светило науки
2013-07-17T05:13:50+00:00

1)    15  -  x   -  2x^2  >  0

         2x^2  +  2x  -  15  <  0

         2x^2  +  2x  -  15  =  0

         D  =  b^2  -  4ac  = 2^2  -4*2*(-15)  =  4  +  120  =  124>0

         x_1  =  (-b  +  VD)/2a  =  (-2  +  V4*31)/2*2  =  (-2  +  2V31)/4  =  2(-1  +  V31)/4  = 

                 =  (-1  +  V31)/2

          x_2  =  (-b  -  VD)/2a  =  (-1  -  V31)/2

          Решением  является       (-1  -   V31)/2  <  x   <  (1  +  V31)/2

Ответ.         ( (-1  -  V31)/2;        (-1  +  V31)/2 )